PENGARUH RADIASI MATAHARI PADA AIR LAUT TERHADAP DAYA YANG DIHASILKAN SEBAGAI SUMBER ENERGI ALTERNATIF - Eva Meutia; Upik Nurbaiti; Fianti Fianti (EnviroScienteae, 2021)
Indonesia with a country that has a tropical climate and a very large intensity of solar radiation so that it can be developed into an alternative energy source by utilizing sea air. The purpose of this research is whether there is an effect of solar radiation on sea air on the power it produces as an alternative energy. Seawater as much as 300ml is put into a square glass container and paired with a series of Cu - Zn, Cu - Al, and Al - CuZn electrode plates with a cross-sectional area of 15cm2 of each electrode and connected to a red LED light to see how much power is generated by sea water after being exposed to solar radiation at different temperatures and times. Data obtained at the highest temperature of 33°C and the duration of exposure to solar radiation for 60 minutes in the 6th experiment with a variation of Cu - Zn electrodes with an electric power of 1,44 J/s, the lights are brightly lit, Cu - Al with electric power of 1,22 J/s of dim light, and Al - CuZn obtained electric power of 0,65 J/s. So it is concluded that the longer the sea water is exposed to solar radiation, the higher the temperature is due to the more heat stored in sea water. The conclusion was drawn that the higher the sea water temperature, the electric power produced, the higher the electric power generated and the lights can light up brightly at certain electrodes.